The Effectiveness of the Team Assisted Individualization (TAI) Cooperative Learning Model with a Contextual Approach to Student Problem Solving at SMPN 1 Bringin - Binti Nur Cahyanti; Budi Sasomo; Arum Dwi Rahmawati (ASIAN: Indonesian Journal of Learning Development and Innovation, 2024)
This research was conducted at SMP Negeri 1 Bringin. This study aims to determine the effectiveness of the Team Assisted Individualization (TAI) cooperative learning model with a contextual approach to student problem solving. This research was conducted in class VIII, with a population of all classes VIII A to F. The sample of this study was class VIII D, as the experimental class and class VIII F as the control class. This study used a quasi-experimental quantitative research design, namely a posttest only control group design where researchers gave posttests to both the experimental and control classes, but only the experimental group received treatment. The method used in the problem-solving stages of this study is Polya's four stages. By using data analysis at a significance level (α) = 0.05, the hypothesis results were 2.885> 2.056 with the conclusion that in class VIII D or the experimental class Ho was rejected and Ha was accepted, then the Team Assisted Individualization (TAI) cooperative learning model with a contextual approach was able to improve student problem solving.